An Amazing Algebra Challenge | Can You Solve?
HTML-код
- Опубликовано: 10 фев 2025
- An Amazing Algebra Challenge | Can You Solve?
Welcome to InfyGyan!
Join us in the quartic equation challenge, where we watch quick and efficient solution using algebraic formula's with equation solving tactics! 🚀 Whether you're a student, enthusiast, or problem-solving aficionado, this video breaks down quartic equations in a way that's easy to grasp and apply.
🧠💡 Get ready to conquer the challenge and boost your equation-solving skills!
📚 Topics covered:
Introduction to Quartic Equations
Quick Techniques (identities, substitutions and manipulations) for Solutions
Converting into Quadratic equation
Completing the squares method, complex number
Pro tips for Success
🎓 Level: Beginner to Intermediate
👍 Don't forget to like, share, and subscribe for more math challenges and solutions! Let's dive into the world of quartic equations together! 🤓✨
Additional resources:
• Solving Amazing Quarti...
• How to CRACK This Quar...
• Want To Ace Quartics? ...
• The Easy Way to Solve ...
#quarticequations #canyousolve #matholympiad #problemsolving #mathskills #education #learnmaths #quadraticequations #mathtutorial #algebra #math
We'd love to hear from you! Did you manage to solve the equation? What other math problems would you like us to cover? Let us know in the comments below!
🎓 Happy learning, and see you in the next video! 🎉
Thank you for watching video.
Another approach
Let x = √2•t (*).
The given equation is rewritten as
(√2•t)⁴+(√2•t+√2)⁴=68
4t⁴+4(t+1)⁴=68 t⁴+(t+1)⁴=17
t⁴+2t³+3t²+2t-8=0
(t-1)(t+2)(t²+t+4)=0 by inspection.
t=1 or t=-2 =>
x=√2 or x=-2√2 due to (*).
here a different method,
substitute u=x/√2
u^4+(u+1)^4=2^4+1
soln 1
then make u^4=2^4 and (u+1)^4=1 u=-2
and u^4=1 (u+1)^4=2^4 u=1
X=(-2√2,√2)
Let y=x+√2. Then x^4+y^4=68 and x-y=-√2. Let xy=a. Then, x^4+y^4=2a^2+8a+4=68 which gives a=-8,4. x=-8 does not yield real solutions. For a=4, we get, from x-y=-√2 and xy = 4, x=√2, -2√2.
x = √2 , x = -2√2 real solutions.
The given equation is equivalent to
x⁴+2√2x³+6x²+4√2x-32=0
x³(x+2√2)+2(3x²+2√2x-16)=0
x³(x+2√2)+2[3x(x+2√2)-4√2(x+2√2)=0 (x+2√2)(x³+6x-8√2)=0
x+2√2=0 or x³+6x-8√2=0 =>
x=-2√2 or x=√2.
x³+6x-8√2=x³-2√2+6x-6√2=
x³-(√2)³+6(x-√2)=
(x-√2)(x²+√2•x+√2²)+6(x-√2)=
(x-√2)(x²+√2•x+8)=0 => x=√2 etc . .
x + (√2)/2 = u => x = u - (√2)/2
[u - (√2)/2]⁴ + [u + (√2)/2]⁴ = 68
2(u⁴ + 3u² + 1/4) = 68
u⁴ + 3u² - 135/4 = 0
u² = (-3 + 12)/2
u² = 9/2 => u = ±(3√2)/2
u = (3√2)/2
x = (3√2)/2 - (√2)/2
*x = √2*
u = (-3√2)/2
x = (-3√2)/2 - (√2)/2
*x = -2√2*
x^4 +(x^4+20)={x^4+x^4 ➖ }+20x^4={x^8+20x^4}=20x^12 4^4^4^4^4x^4^8 2^2^2^2^2^2^2^2^2^2x^2^2^2^3 1^1^1^1^1^1^1^1^1^1x^1^1^1^1^2 1x^1^2 1x^2 (x ➖ 2x+1).
Η λυση στη φωτο. (βαριεμαι να ξαναγραφω)
for Quick solution:
x⁴+(x+√2)⁴=68=(4+64) or (64+4); =>x⁴=4 or 64;
=> x⁴=(√2)⁴ or (2√2)⁴;=>
x = ±√2; or; ±2√2; verify>
for x =±√2; (x+√2)⁴=64; => x +√2=2√2;=>x=√2;
x=-√2 not verified >rej.
for x=±2√2 =>x=-2√2 is
Verified, & 2√2 not ver.
x = √2 or -2√2